Differential Associations of IL-4 With Hippocampal Subfields in Mild Cognitive Impairment and Alzheimer’s Disease - Boccardi, Virginia; Westman, Eric; Pelini, Luca; Lindberg, Olof; Muehlboeck, J-Sebastian; Simmons, Andrew; Tarducci, Roberto; Floridi, Piero; Chiarini, Pietro; Soininen, Hilkka; Kloszewska, Iwona; Tsolaki, Magda; et al. (Frontiers in Aging Neuroscience, 2019)
Background/Aims: We aimed to assess the association between in volumetric measures of hippocampal sub-regions – in healthy older controls (HC), subjects with mild cognitive impairment (MCI) and AD- with circulating levels of IL-4. Methods: From AddNeuroMed Project 113 HC, 101 stable MCI (sMCI), 22 converter MCI (cMCI) and 119 AD were included. Hippocampal subfield volumes were analyzed using Freesurfer 6.0.0 on high-resolution sagittal 3D-T1W MP-RAGE acquisitions. Plasmatic IL-4 was measured using ELISA assay. Results: IL-4 was found to be (a) positively associate with left subiculum volume (β = 0.226, p = 0.037) in sMCI and (b) negatively associate with left subiculum volume (β = -0.253, p = 0.011) and left presubiculum volume (β = -0.257, p = 0.011) in AD. Conclusion: Our results indicate a potential neuroprotective effect of IL-4 on the areas of the hippocampus more vulnerable to aging and neurodegeneration.